2003
DOI: 10.1101/gr.781503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Imprinted Genes in a Genome-Wide Screen for Maternal Methylation

Abstract: A characteristic of imprinted genes is that the maternal and paternal alleles show differences in methylation. To perform a genome-wide screen for novel imprinted loci, we applied methylation-sensitive representational difference analysis (Me-RDA) to parthenogenetic mouse embryos, to identify differentially methylated regions (DMRs) methylated specifically on the maternal allele. We isolated a total of 26 distinct clones from known and novel DMRs and identified three novel imprinted genes. Nap1l5 is located on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
149
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(161 citation statements)
references
References 48 publications
10
149
1
1
Order By: Relevance
“…It was originally thought that SLC38A4/SNAT4 was a liver-specific isoform (Hatanaka et al, 2001). However, we have shown this isoform is present in human placenta (Desforges et al, 2006) and expression has also been confirmed in rat (Novak et al, 2006a) and mouse placenta (Mizuno et al, 2002;Smith et al, 2003).…”
Section: Molecular Characterisation and Expression In Human Placentamentioning
confidence: 99%
“…It was originally thought that SLC38A4/SNAT4 was a liver-specific isoform (Hatanaka et al, 2001). However, we have shown this isoform is present in human placenta (Desforges et al, 2006) and expression has also been confirmed in rat (Novak et al, 2006a) and mouse placenta (Mizuno et al, 2002;Smith et al, 2003).…”
Section: Molecular Characterisation and Expression In Human Placentamentioning
confidence: 99%
“…The function of NAP1L5 is not known, but its protein shows homology to nucleosome assembly proteins (NAPs) which are involved in cell cycle regulation (Loyola and Almouzni, 2004). The NAP1L5 is paternally expressed in many fetal tissues in human, mouse and cattle (Smith et al, 2003;Zaitoun and Khatib, 2006;Wood et al, 2007). The PPP1R9A encodes neurabin I which is a regulatory subunit of protein phosphatase I, and controls actin cytoskeleton reorganization (Oliver et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic imprinting is a parent-of-origin-dependent epigenetic mechanism, in which a subset of autosomal genes is expressed from only one allele [15]. Imprinted genes have important roles in the regulation of foetal growth, development, function of the placenta and postnatal behaviour, in mammals in particular [14].…”
Section: Introductionmentioning
confidence: 99%